Kajian Ekologi Spiritual untuk Menjembatani Alkitab dan Sains dalam Mengatasi Polusi Udara - Tjokrohandoko, Soewarto; Harefa, Otieli (Shift Key : Jurnal Teologi dan Pelayanan, 2024)
Intensive exploitation of natural resources has triggered a global environmental crisis. This study analyzes the biblical perspective on the human relationship with nature to find a theological foundation for environmental conservation. Through a literature review, it was found that the Bible teaches humans to live in harmony with nature as part of God's creation. This study highlights the concept of stewardship as a relevant theological framework for addressing environmental problems, particularly air pollution. The results of this study   contribute to the development of faith-based environmental ethics and can inspire the development of sustainable policies and educational programs.